Hubungan Gaya Belajar dan Motivasi Belajar dengan Minat Belajar Siswa di UPT SMP Negeri 1 Silahisabungan Kabupaten Dairi - Aldo Rihdo Adytia Lubis; Hasanuddin Hasanuddin; Suaidah Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to analyze the relationship between learning styles and learning motivation with student interest in learning at UPT SMP Negeri 1 Silahisabungan, Dairi Regency. The hypothesis proposed is that there is a positive relationship between learning styles and students' learning motivation with student interest in learning at UPT SMP Negeri 1 Silahisabungan. The number of samples used in this study were 162 samples of respondents/students at UPT SMP Negeri 1 Silahisabungan with simple random sampling. The data collection technique used is spreading google form and then analyzed by statistical analysis method with regression analysis of two predictors. Based on the results of data analysis shows that: there is a relationship between learning styles and interest in learning, with a significant correlation of 9% affecting interest in learning. There is a relationship between learning motivation and interest in learning, with a significant correlation of 35% affecting interest in learning. There is a relationship between learning motivation and learning motivation with students' interest in learning, with a significant correlation of 46.1% of the variable's contribution to interest in learning with the remaining 53.9% influenced by other factors. Based on the results of the research above, the proposed hypothesis is declared accepted.